Sources of Monetary Growth Uncertainty and Economic Activity: The Time- Varying-Parameter Model with Heteroskedastic Disturbances - Kim, Chang-Jin (The Review of Economics and Statistics, 1993)
Chang-Jin Kim, Sources of Monetary Growth Uncertainty and Economic Activity: The Time- Varying-Parameter Model with Heteroskedastic Disturbances, The Review of Economics and Statistics, Vol. 75, No. 3 (Aug., 1993), pp. 483-492